Evolusi Kurikulum Pesantren dalam Tekanan Politik Pendidikan Kolonial Belanda - Alya Maisara; Dirwansyah Dirwansyah; Nur Afifah; Idrus L (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the evolution of pesantren curriculum within the context of Dutch colonial educational politics through a historical-critical literature review approach. The research analyzes how pesantren institutions responded to external political pressures while maintaining their religious identity and educational autonomy. The findings reveal that curriculum transformation in pesantren was not merely reactive but constituted a complex process of reconstruction involving selective integration between Islamic traditional knowledge and modern educational elements. Mechanisms such as muadalah, curriculum integration, and the central role of kiai functioned as key drivers in shaping adaptive and context-sensitive curricular models. Furthermore, regional variations demonstrate that pesantren evolution followed diverse trajectories influenced by socio-cultural, institutional, and resource-based factors. These transformations contributed to the emergence of pesantren as hybrid educational institutions capable of bridging religious traditions with national education systems. The study highlights that pesantren curriculum evolution represents a form of epistemological resilience, enabling Islamic education to remain relevant amid changing political and educational landscapes.